Pengaruh Motivasi, Kompetensi dan Disiplin Kerja Terhadap Kinerja Karyawan PT. Jomonal Negelem Negel Papua - Kharin Rahmatika; Widarta Widarta (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze the effect of work motivation, work competence, and work discipline on employee performance at PT. Jomonal Negelem Negel Papua, both partially and simultaneously. This research employs a quantitative approach using a survey method. The population consists of all employees of PT. Jomonal Negelem Negel Papua totaling 105 employees, with a sample of 84 respondents determined using the Slovin formula and simple random sampling technique. Data were collected through questionnaires using a Likert scale. The data analysis techniques include validity test, reliability test, classical assumption test, multiple linear regression analysis, t-test, F-test, and coefficient of determination (R²), processed using SPSS software. The results indicate that work motivation, work competence, and work discipline partially have a positive and significant effect on employee performance. Simultaneously, work motivation, work competence, and work discipline also have a significant effect on employee performance at PT. Jomonal Negelem Negel Papua. These findings suggest that employee performance can be improved by strengthening work motivation, enhancing work competence, and consistently implementing work discipline. This study is expected to contribute to the development of human resource management and provide practical input for company management in improving employee performance.